The Perfect Score - Robbins, Brian, 1963-; Christensen, Erik, 1945-; Chris Evans; Bryan Greenberg; Scarlett Johansson; Darius Miles; Leonardo Nam; Tyra Ferrell; Matthew Lillard; Vanessa Angel; Bill Mackenzie; Dan Zukovic; et al. (USA Paramount Pictures, 2004)
It's a film about 6 teenagers from diverse backgrounds - among them the school's star basketball player - who conspire to break into a SAT testing center to steal the answers in hope of acing their exam. They quickly realize that the answer to their problems and the key to their happiness do not lie in achieving a perfect score.
Language(s): English, Turkish, German Subtitle(s): English, Turkish, German
Keywords: Comedy; Crime